ECONOMIC IMPACT OF INFECTIOUS LARYNGOTRACHEITIS IN A COMMERCIAL LAYER FARM IN LIMA, PERU - Alvarado E., Jessica (2013)
The aim of this study was to evaluate the economic impact caused by avian infectious laryngotracheitis (ILT) in a commercial layer farm located in the district of Chilca, Lima, with a population of 14 415 hens that was affected by the ILT from August 2008 to March 2010. A survey was conducted and visits to the farm were done to collect biosafety and production data, and production costs of the campaign with ILT and the previous campaign without ILT. The economic impact was evaluated by comparing data from both campaigns using a stochastic distribution model with the risk analysis program @ RISK 5.1®. The cost per kilogram of eggs increased by 34%, egg production declined by 16%, and mortality increased by 18% in the campaign with ILT.